East Asia a new history - Murphey, Rhoads 1919- (Addison Wesley Longman, Inc., 1996)
Engaging, integrated, and analytical, East Asia: A New History provides a comprehensive history of the East Asian countries and addresses a diverse range of social, economic, and intellectual histories. Several unique features of the text [are] a concluding section on the "Pacific century" to reflect an absolutely current perspective; significant material on influential women in East Asian history as well as gender issues; and a generous program of boxed document excerpts that expose students to the voices of key figures and writers in East Asian history.